1995
DOI: 10.1093/jac/35.1.95
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro and in-vivo selection of Staphylococcus aureus mutants resistant to ciprofloxacin

Abstract: Staphylococcus aureus mutants resistant to ciprofloxacin were selected both in vitro and in vivo. In-vitro selection was achieved by incubating two strains of S. aureus (MICs of ciprofloxacin of 0.5 and 4 mg/L respectively) in the presence of ciprofloxacin in concentrations equivalent to 1/2 x MIC for 24 h and isolating the mutants on agar containing the quinolone at 1, 2 or 5 x MIC. Stably-resistant mutants of both strains were isolated, although the frequency of mutation of the susceptible strain was higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In addition, strains of the organism resistant to sulfisoxazole, which is the antimicrobial recommended as an alternative agent for its treatment [4], were isolated by a stepwise procedure [5]. In in vitro and in vivo studies on bacteria, mutant resistant Staphylococcus aureus were able to be selected with exposure to a sub-MIC of ciprofloxacin [10]. These studies offered important information, because some C. trachomatis strains may have the potential to develop resistance to fluoroquinolone when they are exposed to fluoroquinolone in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, strains of the organism resistant to sulfisoxazole, which is the antimicrobial recommended as an alternative agent for its treatment [4], were isolated by a stepwise procedure [5]. In in vitro and in vivo studies on bacteria, mutant resistant Staphylococcus aureus were able to be selected with exposure to a sub-MIC of ciprofloxacin [10]. These studies offered important information, because some C. trachomatis strains may have the potential to develop resistance to fluoroquinolone when they are exposed to fluoroquinolone in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Doss et al [4] reported that resistant mutants, which persisted even after treatment was discontinued, were selected in their study, which was designed to obtain subinhibitory concentrations of ciprofloxacin in subcutaneous abscess cavities. Thus, it is justified to speculate that the failure of an empirical therapy for UTI may partly depend on a situation in Takahashi/Hirose/Sano/Nishimura/ Matsukawa/Mikami/Tsukamoto which the less susceptible strains were selected and multiplied under the conditions of sub-MIC antibacterial exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Ciprofloxacin-, trimethoprim-and sulphonamide-resistant mutants were selected according to the method used by Doss et al 5 Each of the study strains was inoculated into Iso-sensitest broth containing ciprofloxacin, trimethoprim, sulphadiazine and sulphamethoxazole alone or in combination at concentrations equivalent to 0.5 MIC. After 24 h, 0.1 mL aliquots were subcultured on to Iso-sensitest agar containing either no antibacterial or antibacterials, singly or in combination, at concentrations equivalent to 1, 2 or 5 MIC for each strain.…”
Section: In-vitro Development Of Resistancementioning
confidence: 99%
“…Fluoroquinolones initially provided effective therapy with patient convenience but became limited with use because of rapidly increasing bacterial resistance. [3][4][5][6] The aim of the present investigation was to determine the in-vitro effectiveness of an oral therapy consisting of a combination of ciprofloxacin with trimethoprim and…”
Section: Introductionmentioning
confidence: 99%